QoS enhancement based on resource allocation in wireless networks - Chaari, Hekma; Mnif, Kais; Zarai, Faouzi; Kamoun, Lotfi (2017 13th International Wireless Communications and Mobile Computing Conference, IWCMC 2017, 2017)
Given wireless networks struggle with limited radio resources, to be able to transmit multimedia applications with specified Quality of service 'QoS' requirements, including delay constraints, it's important to intensify the need for efficient resource allocation. Therefore, the best solution is to establish a partition of radio resources that provides a minimum quality for each user in the network. Here, it is necessary to establish a concession between the requirements of users and the available resources on the network. This can be achieved within a better radio resource management and the use of optimization techniques. The purpose of this paper is to find a solution that maximizes the quality of transmission by solving the problem of wireless channel partitioning. This solution is based on a technique that provides the optimal source data rate and the optimal bandwidth for each user with a guarantee of QoS requirements. Simulation results show that, using the spectral efficiency parameter for the evaluation, three main parameters must be considered to have the optimal source data rate and the optimal bandwidth, which are delay limit, delay violation probability and SNR average to achieve high spectral efficiency and to exploit optimally the resources of the channel.
Created from Fastlane, Scopus look-up
Keywords: Delay Violation Probability; Effective Capacity; Resource Allocation; Wireless Networks